DETERMINANTS AND MODERN PECULIARITIES OF LABOR MIGRATION OF RURAL YOUTH - E. S. Kovanova; S. I. Kuzin; O. A. Khokhlova (Вестник университета)
The problems of rural youth and the state of the information base in the field of state youth policy have been considered. A significant problem of the state youth policy is the lack of a system of analysis and social monitoring of the state of the youth environment. A sample survey has shown high labor mobility of the young rural population of the agrarian republic. It has been installed, that the large-scale outflow of rural youth to the city affects negatively on the development of the agricultural cluster of the republic’s economy, especially those in need of young specialists of different profiles. The negative impact on the socio-economic development of the region can have a permanent decline in the number of rural youth, which will subsequently lead to a reduction in the number of rural population.